The Role of Social Media in MSME Marketing: A Systematic Literature Review - Bambang Suwarno; Junawan; Syahrial Hasanuddin Pohan (Yayasan Multidimensi Kreatif, 2025)
This Systematic Literature Review (SLR), following the PRISMA methodology, examines the impact of social media marketing on the performance, sustainability, and resilience of Micro, Small, and Medium Enterprises (MSMEs), synthesizing findings from 12 studies published between 2001 and 2025. The review highlights that social media marketing adoption significantly enhances MSME performance, improving customer engagement, brand visibility, and market reach. Entrepreneurial orientation is identified as a crucial moderating factor, strengthening the effect of digital marketing adoption on business outcomes, particularly in response to disruptions like the COVID-19 pandemic. Furthermore, the adoption of e-commerce and digital marketing tools contributes positively to financial and sustainability performance, though digital literacy and resource constraints remain key barriers. The findings also underscore the importance of networking and informal marketing practices in expanding market presence and fostering customer relationships. Despite the positive effects, challenges such as limited resources and digital skills hinder the full potential of these strategies. This review calls for future research to address these gaps, focus on sector-specific practices, and explore the long-term impact of social media marketing on MSME resilience and sustainability.